The Kinase Complex mTOR Complex 2 Promotes the Follicular Migration and Functional Maturation of Differentiated Follicular Helper CD4+ T Cells During Viral Infection - Hao, Yaxing; Wang, Yifei; Liu, Xiaobing; Yang, Xia; Wang, Pengcheng; Tian, Qin; Bai, Qiang; Chen, Xiangyu; Li, Zhirong; Wu, Jialin; Xie, Zhunyi; Zhou, Xinyuan; et al. (Frontiers in Immunology, 2018)
Follicular helper CD4+ T (TFH) cells are critical for optimal B-cell-mediated humoral immunity by initiating, fueling and sustaining germinal center reactions. The differentiation of TFH cells relies on multiple intrinsic and extrinsic factors; however, the details by which these factors are integrated to coordinate TFH differentiation are largely unknown. In this study, using a mouse model of acute LCMV viral infection, we demonstrate that mTORC2 kinase integrates TCR signaling and ICOS-mediated co-stimulation to promote late differentiation and functional maturation of virus-specific TFH cells. Specifically, mTORC2 functions to maintain TFH lineage specifications, including phenotype, migratory characteristics and functional properties. Thus, our results highlight the importance of mTORC2 in guarding TFH phenotypic and functional maturation.